The Intelligent optimism: a theoretical approach to its scope (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2025)
In the present article, the need to seek attitudinal tools that allow people to face challenges in a positive way is proposed, recognizing problems, shortcomings or weaknesses and working on overcoming them, with theories such as intelligent optimism providing the necessary answers. This study is documentary in nature under a bibliographic design and is carried out based on the collection of information in books and scientific articles to conduct a content analysis through critical reading, opinion and interpretation of the researcher, making a summary or synthesis in which the relevant aspects and clear conclusions were pointed out. The purpose of the article is to describe the theoretical scope of intelligent optimism as an attitude in the transformation of people to face adversities. It is concluded that optimism can be learned and has a direct impact on the way we face situations. Additionally, intelligent optimism includes a critical and realistic component, which does not remain in seeking the positive side of situations with generative thinking, but also evaluates difficulties and acts adaptively. Therefore, its implementation promotes a positive attitude, based on reality and action.
Keywords: intelligent optimism; positive psychology; generative thinking